Work-Life Balance versus Work-Life Integration: Which Satisfies More for Gen Z? - Ahmad Shalahuddin; Ilzar Daud (Global Research Collaboration, 2026)
The changing nature of work has raised questions about whether Gen Z employees are more satisfied when they maintain clear work-life boundaries or when they integrate work and personal roles flexibly. This study examines the effects of work-life balance and work-life integration on job satisfaction among Gen Z employees and compares their relative predictive strength across employment sectors. A quantitative explanatory design was used with survey data from 250 Gen Z employees born between 1997 and 2007. Data were collected through Google Form distributed via LinkedIn and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings show that both work-life balance and work-life integration positively affect job satisfaction. However, work-life balance has a stronger effect, indicating that boundary control, personal recovery time, and manageable work demands remain more important than flexible role blending. Sectoral comparison also shows meaningful differences, with Tech and Education employees reporting higher satisfaction than Healthcare and Retail employees. The study concludes that flexibility should not be treated as a universal solution for Gen Z employee satisfaction. Organizations need to design work-life policies that combine flexibility with clear boundaries, predictable workloads, and respect for non-working time. This study contributes to work-life research by distinguishing balance from integration and showing that sectoral work conditions shape how Gen Z employees experience job satisfaction.